2018
DOI: 10.1016/j.ijbiomac.2018.09.185
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the mucoadhesive properties of chitosan nanoparticles prepared using different chitosan to tripolyphosphate (CS:TPP) ratios

Abstract:  the interactions between CS:TPP nanoparticles and mucin were evaluated  the degree of interaction depends on the CS:TPP ratio, -potential and viscosity  a CS:TPP ratio of 4:1 displayed the strongest interaction with mucin  greater mucin binding efficiencies achieved at CS:TPP ratios of 4:1 and higher  a minimum CS:TPP ratio of 4:1 is required for stable interactions with mucin 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(40 citation statements)
references
References 56 publications
(79 reference statements)
1
28
0
Order By: Relevance
“…Mucin alone has a negative ζ-potential: −18.7 ± 0.6 mV [187], which is very close to the value of −19.4 mV (at pH 7) that was reported from Sogias et al [54]. CS has a positive ζ-potential close to +46.7 ± 0.4 mV, which decreases progressively by increasing the amount of TPP used for NPs preparation (vide supra) [188]. As the number of available -NH 3 + groups-which are able to ionically interact with the sialic acids of mucin-decrease, a reduced mucoadhesion is expected.…”
Section: Nanoparticles From Modified Chitosansupporting
confidence: 83%
“…Mucin alone has a negative ζ-potential: −18.7 ± 0.6 mV [187], which is very close to the value of −19.4 mV (at pH 7) that was reported from Sogias et al [54]. CS has a positive ζ-potential close to +46.7 ± 0.4 mV, which decreases progressively by increasing the amount of TPP used for NPs preparation (vide supra) [188]. As the number of available -NH 3 + groups-which are able to ionically interact with the sialic acids of mucin-decrease, a reduced mucoadhesion is expected.…”
Section: Nanoparticles From Modified Chitosansupporting
confidence: 83%
“…The optimal vectors not only protect the MB from degradation but also mediate target recognition of nucleic acid sequences in the cells, thereby facilitating the visualization study of live cells. CS has low toxicity and immunogenicity and can be obtained in a large quantity from the natural environment (Hejjaji et al 2019). Due to its polycationic characteristics, chitosan can form complexes with negatively charged nucleic acids through electrostatic interactions, leading to the condensation and protection of nucleic acids.…”
Section: Discussionmentioning
confidence: 99%
“…It relies on electrostatic interactions between the positive charges on chitosan and the negative charges on a non-toxic cross-linker, such as sodium tripolyphosphate (TPP) [ 26 ]. When using this technique, the determination of the ratio Cs/TPP and pH of the solution is key for optimizing NPs’ physicochemical properties, such as size and zeta potential (ZP) [ 27 ]. Indeed, the size and ZP play a key role in the endocytosis of NPs by brain endothelial cells since it was found that, to be effective in crossing the BBB, NPs should have a size smaller than 200 nm and a positive ZP value [ 28 , 29 ].…”
Section: Chitosan Nanocarriersmentioning
confidence: 99%